Digitalisasi Zakatnomics: Community-Based Mustahik Economic Empowerment (An Economic Empowerment Chain Study) - Rahayu, Nurul Widyawati Islami; Adhim, Fauzan (International Journal of Artificial Intelligence Research, 2024)
Zakatnomics is a management model of zakat, infak, and alms for improving economic productivity. The strategic role of zakat as Islamic Social Finance has not so far made any significant improvement on the mustahik (zakat beneficiaries) economy. This condition requires lessons learned from various success stories of zakat management in alleviating poverty. On this basis, this study aimed to explore the process of economic empowerment of zakat mustahik carried out by BAZNAS Jember in its target groups in SDG villages in aspects of existing community strategies, production, and marketing. This research employed qualitative approaches focusing on ethical and emic data collected by interviews, FGDs, observations, and documentation techniques. Specifically, the study used Creswell's spiral data analysis. This study produced three descriptive findings: First, the Existing Community Strategy includes 1) the presence of local leaders to supervise the process on-site, 2) creating income management and sharing to support members' daily finances, 3) utilizing supporting activities to build member solidity and education, and 4) social empathy to foster member care. Second, production development included 1) legality for business formalization 2) optimization for increasing value, and 3) expert assistance to encourage member enthusiasm with external quality assurance. Third, the marketing strategy included 1) direct marketing by combing the local market and 2) marketing integration, supporting the needs of implementing the BAZNAS Jember program